Field Distribution of Environment and Vibration Chamber - Wang Tong; Guan Yin; Xu He Xu He; Liang Qiong-chong (Universitas Ahmad Dahlan, 2012)
Environment and vibration test system can test equipment such as radars in full load condition. Environment and vibration chamber is an opening rectangular cavity. In order to study the field distribution of environment and vibration chamber, the open rectangular cavity field distribution and parabolic antenna are analyzed by using the Dyadic Green’s functions. According to the Dyadic Green’s functions, the field distribution of environment and vibration chamber is concluded by MATLAB. The simulation result of FEKO proves that the method by using Dyadic Green’s functions is available. The innovation of this article is using the Dyadic Green’s functions to analyzed open cavity field and parabolic antenna.